Pengukuran Kinerja Mesin Sewage Treatment Plant (STP) menggunakan Metode Overall Equipment Efeectiveness : (Studi Kasus Pada PT. Gaia Care International) - Sofyan Wahyu; Nova Pangastuti; Sepriadi Paningotan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
One of the important things in supporting the operational management of the building which is part of the building's mechanical and electrical aspects is the building's domestic liquid waste management system. The availability of liquid waste production cannot be separated from the performance of the Sewage Treatment Plan (STP) machine as a work tool that produces domestic liquid waste production in HDI Hive Menteng Building. STP machine maintenance is one of the important factors in ensuring the quality of liquid waste production in accordance with the Environmental Service (DLH) quality standards. The machine maintenance system can be used as a benchmark for measuring the effectiveness of STP machines. Machine performance with a high rhythm without stopping 24 hours which continues to increase and is comparable to the tenant accoupancy level, of course requires anticipatory action for machine breakdown problems. Overall Equipment Effectiveness (OEE) is a method used to measure and maximize machine effectiveness based on three categories, namely Availability rate, Performance rate, Quality rate. From the results of calculating the OEE value for the STP machine at PT. Gaia Care International) of 82.96%, in general the OEE value is still below the JIPM standard value, namely greater than 85%. For this reason, in this research, an analysis was carried out using a fishbone diagram, which is used to determine the causes and effects of not achieving the effectiveness of the STP machine. Based on the results of the Fish Bone Diagram analysis with several factors including; Machines, methods, people and materials can be concluded as factors that cause a decrease in the OEE value of STP machines, namely rework losses which are quite high so that they affect the Quality OEE value in STP machine measurements. The proposal given to increase the effectiveness of the STP Machine for controlling Rework Losses is to improve the general cleaning routine and increase the Backwash Pump Capacity in the aeration tank and Inlet.